Spatiotemporal variation in the blood lead levels of Chinese children with the environmental Kuznets curve trend. Issue 11 (November 2022) - Liu, Yang; Xu, Chengdong; Liu, Feiyan; Shen, Fengbei; Zhang, Boya; Zhang, Jingyi; Xiao, Gexin; Wang, Ning; Lin, Ni; Zhou, Shaoqi; Wang, Huijun; Du, Qingfeng
Abstract: The environmental Kuznets curve (EKC) is often used to analyze the relationship between environmental pollution health indicators and economic development level in different regions. In developed countries, the blood lead levels (BLLs) of children have been declining fitting the EKC since the 1970s. However, such figures in China have remained at relatively high levels, without any obvious decline, since 2010. We explored spatial variations and graded countermeasures using reported data on BLLs including the lead poisoning rates (LPRs) of children. We found that there were prefectures where either the mean BLLs of the children had reached 100.00 μg/L or the LPRs of more than 40% of the children had reached 100 μg/L. When we reduced the average BLLs to 50 μg/L or lowered the proportion of children with a lead poisoning rate (LPR) above 100 μg/L to 10.00%, the EKC trend decreased, and the linear slope after 2010 became -0.202. If the areas where children's BLLs exceeded 50.00 μg/L or the proportion of children with an LPR above 100 μg/L was more than 10.00% will be controlled, the linear slope of the EKC decrease trend after 2010 will became -0.989, and the national average of children's BLLs would decline by 22.17%. The study concluded that children's BLLs in different regions of China are situated at different EKC stages, and urgent prevention and control strategies must be put in place for undeveloped areas. Abstract : Blood lead levels; Spatial variation; Environmental Kuznets curve; Regional sustainable development; China.